Cost-Effectiveness of Sequential Teriparatide/Zoledronic Acid Compared With Zoledronic Acid Monotherapy for Postmenopausal Osteoporotic Women in China - Ruxu You; Jinyu Liu; Lei Ke; Guangyi Yu; Yu Zhang; Takahiro Mori; Takahiro Mori; Takahiro Mori (Frontiers Media S.A., 2022)
ObjectiveWe aimed to assess the cost-effectiveness of sequential teriparatide/zoledronic acid relative to zoledronic acid monotherapy for postmenopausal osteoporotic women in China.MethodsA previously validated Markov microsimulation model was updated to examine the cost-effectiveness of daily subcutaneous teriparatide for 2 years followed by annual intravenous zoledronic acid for 3 years (sequential teriparatide/zoledronic acid), compared with zoledronic acid monotherapy for 3 years in Chinese women with postmenopausal osteoporosis at ages 65, 70, 75, and 80 from the health care payer perspective.ResultsThe incremental cost-effectiveness ratios (ICERs) (US dollars [$] per quality-adjusted life-year [QALY]) of sequential teriparatide/zoledronic acid vs. zoledronic acid monotherapy was $173,223/QALY at age 65 years, which was much higher than the pre-determined willingness-to-pay (WTP) threshold of $ 31,512/QALY, and the results were similar at other ages. In one-way sensitivity analyses, the two most impactful parameters were the cost of teriparatide and the residual effects of the medications included in this study. Sequential teriparatide/zoledronic acid became cost-effective at age 80 with the cost of teriparatide reduced by 50%. Without the residual effect, the ICER increased to $257,982/QALY. Probabilistic sensitivity analyses shown that the probabilities of zoledronic acid monotherapy being cost-effective were 100% at a WTP of $31,512/QALY.ConclusionsAmong Chinese women with postmenopausal osteoporosis, sequential teriparatide/zoledronic acid was not cost-effective unless the cost of teriparatide was reduced by 50% only for the participants over 80 years.